Pengaruh Kompensasi dan Iklim Organisasi terhadap Kepuasan Kerja - SARI, ELVIERA (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
Competitions amongst International Schools recently become a major concern of School management. The numbers of opening International schools in Jakarta provide a large opportunity of labor market especially those interested in working for a school. Hiring and retaining competent employees are not jobs; school management need to generate an attractive package to attract qualified employees. This research focuses on the job satisfaction from two different perspectives i.e. compensation and organizational climate. This research analyzes the correlation between compensation and organizational climate as factors that provide employee’s job satisfaction at British International School. Descriptive method is used to explore the correlations and identify the attribution of each factor that affects employee’s job satisfactions. The research indicates that compensation and organizational climate strongly affect the job satisfactions.